Volume-dose indexes and dose prescription descriptive review of radiosurgery planning - Pedro Argôlo Piedade (Brazilian Journal of Radiation Sciences, 2019)
In Stereotactic radiosurgery (SRS), indexes are used to compare plans, comparing treatment techniques and evaluate clinical complications. However, they have some limitations and dependencies that need to be well known. Therefore, the analysis using indices is better suited for comparison of plans for the same patient (lesion). The evaluation of stereotactic plans must be undertaken with great care and criteria because there is a huge amount of information between different dose distributions of treatment plans. The objectives are to show some tools for planning analysis in SRS their limitations, some indexes descriptive review in the literature that seek to quantify the three properties mentioned and discuss the concepts involved in SRS dose prescription.